1978
DOI: 10.1016/0020-7683(78)90035-5
|View full text |Cite
|
Sign up to set email alerts
|

Can two solids slide without slipping?

Abstract: Abstract-Thequestion posed is whether two solids that are pressed together and at the same time sheared can undergo a sliding motion without \lip al the interface. The mechanism involves a propagating separation zone, with the tangential shift between the solids taking place in this zone whilst they are out of contact. It is shown that the applied forces can sustain such motion, and that the separation zones can propagate with velocities above the speed of surface waves and also in the transonic range. If such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…However, Comninou and Dundurs showed that steady-state solutions of this form are only possible if square-root singular tractions are admitted. In a later paper [16], they also showed that a disturbance of a more general form could propagate at a frictional interface without slip, under the same assumptions.…”
Section: Energy Considerationsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, Comninou and Dundurs showed that steady-state solutions of this form are only possible if square-root singular tractions are admitted. In a later paper [16], they also showed that a disturbance of a more general form could propagate at a frictional interface without slip, under the same assumptions.…”
Section: Energy Considerationsmentioning
confidence: 96%
“…Also, in the interface wave problem [14,16], non-uniqueness is suggested by the fact that waves can be found which propagate at any speed within a given range, whereas in the absence of separation, there is a unique propagation speed. Non-uniqueness of solution is acceptable if it is associated with historydependence of solution and, in this context, Comninou and Dundurs [17] suggest that the wave propagation speed depends on conditions at the initiation of the disturbance.…”
Section: Non-uniquenessmentioning
confidence: 99%
“…We know that the amount of gouge produced is small. For a conservative estimate, assume that during any The other possibility is that the normal stress is significantly reduced near the tip of the moving slip dislocation via the action of interface separation waves [Comninou and Dundurs, 1978]. While this possibility has been questioned on theoretical grounds [Freund, 1978], experiments on foam rubber models show interface separation waves [Brune et al, 1993] and reduced heat production during stick slip [Anooshehpoor and Brune, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…Amontons' law is explained as resulting from the increase in the total area of real contact points, that is, the real contact area, in proportion to the loading force and the constant binding energy per unit real contact area1234567. However, the mechanism and the validity of Amontons' law are still discussed actively2345678910111213.…”
mentioning
confidence: 99%